Investigation Of The Prognostic Value Of The Neutrophil/Lymphocyte Ratio In Bell Palsy - Dizdar, Denizhan; Özgür Avınçsal, Mehmet; Kurt Dizdar, Senem (ENT Updates, 2018)
Objectives: Bell palsy (BP), also known as idiopathic facial paralysis, is a unilateral, acute-onset, isolated lower motor neuron weakness. It accounts for 60% to 75% of all cases of unilateral facial paralysis. The estimated annual incidence ranges between 11 and 40 per 100.000 people, with 40.000 new cases each year in different parts of the world. The neutrophil/lymphocyte ratio (NLR), calculated as the ratio of absolute neutrophil count to absolute lymphocyte count, is an easily measurable and inexpensive systemic inflammation marker. This study investigated the association between the NLR and BP by comparing clinical characteristics and functional outcomes of patients with BP and healthy controls. Methods: Thirty patients (24 women, 6 men) who presented to our clinic with BP between 2014 and 2016 were included in the study. The subjects underwent a general physical examination and an assessment of laboratory blood parameters. All patients were treated with prednisone, 1 mg/kg per day with a progressive dose reduction. The NLR was calculated as the simple ratio between absolute neutrophil and absolute lymphocyte counts. Results: The mean (SD) NLR values were 2.141 (0.80) in patients with BP and 1.41 (0.46) in the control group. The difference between groups was significant (p=0.0001). There was a positive correlation between grade of facial paralysis and NLR values (r=0.663, p=0.0001). There was a positive correlation between prognosis of facial paralysis and NLR values (r=0.239, p=0.0251). Conclusion: The NLR was a valuable marker in BP patients in this study. Moreover, this study demonstrated a linear relationship between the NLR and BP severity and prognosis.